The hundred secret senses - Tan, Amy (New York : G. P. Putnam's Sons, 1995)
The story of two sisters, one brought up in the U.S., the other in China. The American sister is contemptuous of the other's belief in ghosts until events cause her to understand what they can do.
Keywords: Chinese American women -- Fiction; Domestic fiction